Estimation of Educational Requirements in Occupations and Occupational Groups - Weiermair, K. (Relations industrielles / Industrial Relations, 1974)
This paper explores the usefulness of employer surveys for purposes of assessing and forecasting educational needs in occupations and occupational groups.